(untitled) (Scientific journal of the Fergana State University, 2024)
This article provides information about international assessment programs, changes in the field of education in our country, PIRLS and TIMSS and other assessment programs, information about the role of international assessment programs in ensuring the quality of education in mastering subjects of elementary school students. . Also, the conditions of origin of these evaluation programs and the legal basis of their application in our country were discussed.